Ibiza, Spanien: Zum antiken Bleiglanzabbau am Puig de s’Argentera - Hermanns, Marcus H. (e-Forschungsberichte des DAI, 2023)
In 2015 the work continued at the northern hillfoot of the Puig de s’Argentera. The main aim was to expand the terrain to be studied and to examine the unearthen relics of mining activities analyzing their context and gaining further hints concerning their date. Therefore, two campaigns took place, the first for four weeks in spring and the second for two weeks in autumn of 2015. This project is part of DAI Cluster II.